PERAN PENYULUH PERTANIAN DALAM PENGEMBANGAN KELOMPOK TANI PADI SAWAH DI DESA LEREPAKO KECAMATAN LAEYA KABUPATEN KONAWE SELATAN - Iwan Setiawan; Musadar Mappasomba; Yoenita Jayadisastra; Putu Arimbawa (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
This study aims to determine the role of agricultural extension workers in the development of rice farming groups in Lerepako Village, Laeya Subdistrict, South Konawe Regency. This study is motivated by the importance of agricultural extension workers as a bridge between farmers and agricultural technology innovations in efforts to increase the productivity and independence of farming groups. The research variables include the role of agricultural extension workers and the development of farming groups. This study uses a descriptive quantitative approach with data collection through questionnaires, observations, interviews, and documentation. The population in this study consists of all active members of farmer groups in Lerepako Village, totaling 195 people. Sampling was conducted randomly using the Slovin formula, with a sample size of 66 respondents. Data analysis was performed using descriptive statistical methods and the Spearman's rank correlation test. The results of the study indicate that the role of agricultural extension workers in Lerepako Village is relatively high across all dimensions of the role measured. On the other hand, farmer group development also showed good results in terms of institutional capacity, agribusiness capabilities, and group functions. The Spearman's rank correlation test confirmed a significant positive relationship between the role of agricultural extension workers and farmer group development. This finding underscores that optimizing the role of extension workers directly impacts the strengthening of capacity and sustainability of farmer groups.